DUMMY CB SEBAGAI ALAT SIMULATOR KUBIKEL UNTUK PEMELIHARAAN PREVENTIF DAN KOREKTIF GUNA MENGURANGI FREKUENSI PADAM PENYULANG 20 KV (APLIKASI PADA SISTEM SCADA 20 KV PT.PLN (PERSERO) APD JATENG & DIY) - Primanto, Meira Dwi; Sasmoko, Priyo (Vocational School Diponegoro University, 2014)
Meira Dwi Primanto, Priyo Sasmoko, in paper dummy CB as cubicle simulator for preventive and corrective maintenance to reduce off frequency 20 KV feeders (20 KV scada system at APD Central Java and Yogyakarta) explain that in 2013, the APD PT.PLN Central Java and Yogyakarta are conducting integration to SCADA at 20 KV feeders in distribution substation. For the next stage has been installed SCADA maintenance should be done periodically. Maintenance can be planned or due to interference with the SCADA system. Maintenance is usually done by the team must perform SCADA Distribution feeder outages and transfer of the load. In the installation of equipment, SCADA team should get a working permit to shut down the feeder, and to transfer the load to another feeder, so that the work has to get permission. SCADA systems are already installed requires maintenance to keep the system reliability. When maintenance SCADA, feeders should be extinguished, whereas for medium voltage customers such as factories, hospitals, and airports should always be channeled electrical energy. Feeder outages and load Delegation KWH lost causes. To the authors attempt to provide solutions that can overcome the missing KWH with a tool innovations made. The author makes a tool such as a dummy circuit breaker simulator 20 KV cubicles. This tool serves Especially when employees perform maintenance or investigation SCADA Disorders, which aims for 20 KV feeders should not be extinguished when performing preventive and corrective maintenance. So the number of frequency of feeder outages can be reduced. Keywords : Dummy Circuit Breaker, 20 KV PMT, SCADA maintenance.